Risk, Efficiency and Performance of Islamic Banking: Empirical Study on Islamic Bank in Indonesia - Sutrisno (Asian Journal of Economic Modelling, 2015)
Banking is an institution that is highly regulated company, both in capital, funding, and liquidity. In this case, bank management must be able to control the risks and efficiency to improve its performance. This study is to examine the effect of risk and efficiency on the performance of Islamic banking. Risk consists of the financing risk that is measured by non-performing financing (NPF),capital risk measured by the capital adequacy ratio (CAR) and liquidity risk is measured by financing to deposit ratio (FDR) and the minimum reserve requirement (RR). The efficiency was measured by operating expenses to operating income ratio (OEOI). While Islamic banking performance was measured by Return On Assets (ROA) and Net Profit Margin (NPM). This study involved 8 Islamic banks in Indonesia as the samples with quarterly data and processed using multiple regression analysis. The results showed the significant effect of FDR, CAR, OEOI and size on the performance of Islamic banking in contrast to the RR and NPF that had no significant effect on the performance of Islamic banking.